2022
DOI: 10.3390/ijerph19095545
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Toxicity of Enrofloxacin on Scenedesmus obliquus in an Aquatic Environment

Abstract: Aquaculture facilities are a potential source of antibiotics in aquatic environments, having adverse effects on the algae species. In this study, the toxicity induced by enrofloxacin (ENR) on the algae Scenedesmus obliquus was evaluated. The uptake of ENR and the change in the growth and photosynthesis of algae were analyzed. At the exposure doses of 10–300 μg/L, the accumulated levels of ENR in algae were 10.61–18.22 μg/g and 12.09–18.34 μg/g after 48 h and 96 h of treatment, respectively. ENR inhibited the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Photosynthetic pigments are essential in assessing the photosynthetic capacity of plants or algae and the extent of environmental stress ( Li et al, 2022 ). After exposing to different concentrations of Cu 2+ , Pb 2+ , and Cd 2+ for 72 h, the contents of photosynthetic pigments, including chlorophyll a (Chla), chlorophyll b (Chlb), total chlorophyll (Ct), and carotenoids (Car), in D. salina were enhanced when Cu 2+ concentration was under 10 mg/L, indicating that low dose of copper could trigger the accumulation of photosynthetic pigments, whereas these pigments declined with the increase in Cu 2+ concentration (>10 mg/L), exhibiting a hormesis effect ( Figure 2 ), which was consistent with the inhibitory effect.…”
Section: Resultsmentioning
confidence: 99%
“…Photosynthetic pigments are essential in assessing the photosynthetic capacity of plants or algae and the extent of environmental stress ( Li et al, 2022 ). After exposing to different concentrations of Cu 2+ , Pb 2+ , and Cd 2+ for 72 h, the contents of photosynthetic pigments, including chlorophyll a (Chla), chlorophyll b (Chlb), total chlorophyll (Ct), and carotenoids (Car), in D. salina were enhanced when Cu 2+ concentration was under 10 mg/L, indicating that low dose of copper could trigger the accumulation of photosynthetic pigments, whereas these pigments declined with the increase in Cu 2+ concentration (>10 mg/L), exhibiting a hormesis effect ( Figure 2 ), which was consistent with the inhibitory effect.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that Scenedesmus is a typical alga with an inducible defense ability, and S. quadricauda can induce the degradation of antibiotics, such as ciprofloxacin and levofloxacin, through biotransformation or biocatalysis by means of decarboxylation and demethylation [ 28 , 29 ], so the relative abundance of S. quadricauda in the ENR concentration of the 200 mg∙L −1 treatment group is relatively high compared with the other treatment groups.…”
Section: Discussionmentioning
confidence: 99%